2005
DOI: 10.1128/mcb.25.22.10122-10135.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Elf1, a Conserved Transcription Elongation Factor in Saccharomyces cerevisiae

Abstract: In order to identify previously unknown transcription elongation factors, a genetic screen was carried out to identify mutations that cause lethality when combined with mutations in the genes encoding the elongation factors TFIIS and Spt6. This screen identified a mutation in YKL160W, hereafter named ELF1 (elongation factor 1). Further analysis identified synthetic lethality between an elf1⌬ mutation and mutations in genes encoding several known elongation factors, including Spt4, Spt5, Spt6, and members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 89 publications
6
85
0
Order By: Relevance
“…This level of cryptic initiation is likely an underestimate of the true level, as this study looked only at coding strands, and the method of detection would have found cryptic initiation only in genes transcribed at low levels Lickwar et al 2009). Cryptic initiation has also been observed in several other mutants, including spt16 and set2 (Kaplan et al 2003;Mason and Struhl 2003;Carrozza et al 2005;Prather et al 2005;Nourani et al 2006;Li et al 2007b;Xiao et al 2007;Cheung et al 2008;Imbeault et al 2008), with spt6 and spt16 mutants having the strongest effects .…”
Section: Spt6 and Fact: Factors Controlling Transcriptional Integritymentioning
confidence: 84%
See 1 more Smart Citation
“…This level of cryptic initiation is likely an underestimate of the true level, as this study looked only at coding strands, and the method of detection would have found cryptic initiation only in genes transcribed at low levels Lickwar et al 2009). Cryptic initiation has also been observed in several other mutants, including spt16 and set2 (Kaplan et al 2003;Mason and Struhl 2003;Carrozza et al 2005;Prather et al 2005;Nourani et al 2006;Li et al 2007b;Xiao et al 2007;Cheung et al 2008;Imbeault et al 2008), with spt6 and spt16 mutants having the strongest effects .…”
Section: Spt6 and Fact: Factors Controlling Transcriptional Integritymentioning
confidence: 84%
“…However, there may be other mechanisms for repression of cryptic promoters, as many mutants that allow cryptic initiation have normal levels of H3K36 methylation . In spt6 mutants, cryptic initiation may be caused by multiple reasons in addition to loss of H3K36 methylation, including an inability to reassemble nucleosomes in the wake of elongating RNAPII (Kaplan et al 2003) and defective recruitment of two factors, Spt2 and Elf1, that each contribute to the repression of cryptic promoters (Prather et al 2005;Nourani et al 2006).…”
Section: Spt6 and Fact: Factors Controlling Transcriptional Integritymentioning
confidence: 99%
“…Their recruitment profile was further analyzed by normalization with pol II (Fig. 1B, bottom panel), and resembled the association pattern of the elongation factors, Spt2, Spt4, Spt5, Spt6, Spt16, and Elf1, all involved in chromatin dynamics, whose association persists over the 3'UTR (14,(16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, at least one of these, the histone chaperone HIRA, has been shown to increase in expression or undergo some level of regulation in aging baboon skin [40,41]. Although the HIRA histone chaperone may have some functions linked to transcription activation [42][43][44][45][46][47][48], this chaperone is known to have an evolutionarily conserved role in heterochromatin formation [49][50][51][52][53][54][55][56].…”
Section: Aging Is Associated With Epigenetic Changes From Yeast To Hmentioning
confidence: 99%